Zastosowanie systemu WASCA w chirurgii refrakcyjnej - Wyględowska-Promieńska, Dorota; Zawojska, Izabela (Klinika Oczna / Acta Ophthalmologica Polonica, 2004)
The WASCA analyzer represents a new generation of diagnostic device for ophthalmology. Using the WASCA analyzer one can diagnose the complete visual performance, including information about higher-order aberrations, not available until now. A plane wave from a lowest-power infrared laser is send into the eye. After performing a passage forward and back in the eye, the existing wave is distorted. The wave front distortion contains complete information about the aberrations of the ocular media, along the optical path of the wave. Only, in an ideal emmetropic and aberration-free eye, the out-coming wave is again a plane one. The measurement is fast and easy to perform.